The Efficiency of WhatsApp in Teleconsultation of Finger Vascularity in Hand Surgery - Raveendran, Sreekanth; Thomas, Binu Prathap; Jayaseelan, Visalakshi (Journal of Hand and Microsurgery, 2019)
Background Teleconsultation over the smartphone is now widely used in modern medicine in the management of burns, flap cover, upper extremity trauma, and in the assessment of the feasibility of reimplantation in amputated fingers. The development of the WhatsApp application has enhanced the smartphone's efficiency remarkably to transmit images in clinical and academic settings with its failsafe and encrypted technology. In hand surgery, a teleconsultation technology must communicate details of finger vascularity effectively. However, there is a paucity of evidence on the functionality of these modern teleconsultation technologies in Hand Surgery. Here, the authors have estimated the efficiency of the WhatsApp teleconsultation in the assessment of finger vascularity.Materials and Methods In two phases, the authors transmitted clinical photographs of vascular and avascular fingers to experienced hand surgeons over the WhatsApp and asked them to assess the finger vascularity. The efficiency of the WhatsApp teleconsultation in assessing the details of finger vascularity was estimated from their responses.Results Despite 81.06% of the hand surgeons rating the vascular fingers on the transmitted photographs correctly, only 44.95% detected the avascular digits accurately; that is, 55.05% of the surgeons failed to diagnose the avascularity of fingers. This suggests serious implications in a clinical setting. The intra- and the inter-rater reliability values were 0.232 and 0.6086 (with 95% confidence interval), respectively, which indicated poor reliability of the WhatsApp teleconsultation regarding the assessment of finger vascularity.Conclusion The authors, therefore, conclude that WhatsApp is inadequate in teleconsultation given the value of vascularity details of the fingers in making a diagnosis in hand surgery.
Keywords: smartphone; WhatsApp; vascularity; hand surgery